Peran Otoritas Jasa Keuangan (OJK) Dalam Mengawasi Dan Menanggulangi Illegal Investments Di Indonesia - Amanda Elda Agustin; Annisa Fitriana; Brilian Dwi Cahyani; Agus Eko Sujianto (Student Research Journal, 2023)
The Financial Services Authority (OJK) is an institution that regulates and supervises financial institutions in Indonesia. However, there are still many deviant investment practices or illegal investments that are currently circulating in the community. This is the responsibility of the Financial Services Authority (OJK) in supervising and tackling illegal investments that occur in Indonesia. This study aims to determine the role of the Financial Services Authority (OJK)’s role in tackling illegal investments in Indonesia. The type of research used is a literature study with a qualitative approach because the data produced is in the form of words or descriptions. Data sources analyzed from time series data use library data collection techniques, reading, recording, and processing research materials. The population in this study is an analysis of related journals.